OPTIMALISASI WAKTU PEKERJAAN PEMBANGUNAN PERUMAHAN GREEN HILL GRESIK MENGGUNAKAN METODE PERT DAN CPM - Siti Masnunah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
This study aims to know the planning to control the project activities during the implementation phase. The success rate or failure of a project leads to less mature planning and less effective controls, resulting in project delays, increased implementation costs and lower quality. To set the time for completion of the project to be more effective and efficient can use PERT and CPM methods so as to reduce the impact of delays and swelling of implementation costs. The PERT (Program Evaluation and Review Technique) method is a method that aims to reduce as much as possible delays, Production, and coordinate various parts of a job thoroughly and accelerate the completion of the project. While the CPM method is a method of planning and control projects that have cost data in the past. Based on the analysis results show the initial duration of the project with duration of 180 days (6 months) with the total cost of Rp. 73.599253,59. As a result of overtime work system, the duration of its activities to be 164 days with project cost of Rp. 55,089,267.07.